Kefir micro-organisms: their role in grain assembly and health properties of fermented milk - Bengoa, Ana Agustina (2019)
Kefir is a homemade viscous and slightly effervescent beverage obtained by milk fermentation with kefir grains, which are built up by a complex community of lactic acid and acetic acid bacteria and yeasts confined in a matrix of proteins and polysaccharides. The present review summarizes the role of kefir micro-organisms in grain assembly and in the beneficial properties attributed to kefir. The use of both culture-dependent and independent methods has made possible to determine the micro-organisms that constitute this ecosystem. Kefir consumption has been associated with a wide range of functional and probiotic properties that could be attributed to the micro-organisms present in kefir and/or to the metabolites synthetized by them during milk fermentation. In this context, the role of micro-organisms in kefir health promoting properties is discussed with particular attention to the contribution of yeast as well as bioactive metabolites such as lactic and acetic acid, exopolysaccharides and bioactive peptides. Even though many advances on the knowledge of this ancient fermented milk have been made, further studies are necessary to elucidate the complex nature of the kefir ecosystem.